A Comprehensive Review of Cross-Linked Gels as Vehicles for Drug Delivery to Treat Central Nervous System Disorders - Leshasha T. Mashabela; Mahlako M. Maboa; Ntombi F. Miya; Taiwo O. Ajayi; Rumbidzai S. Chasara; Marnus Milne; Shoeshoe Mokhele; Patrick H. Demana; Bwalya A. Witika; Xavier Siwe-Noundou; Madan S. Poka (Gels, 2022)
Gels are attractive candidates for drug delivery because they are easily producible while offering sustained and/or controlled drug release through various mechanisms by releasing the therapeutic agent at the site of action or absorption. Gels can be classified based on various characteristics including the nature of solvents used during preparation and the method of cross-linking. The development of novel gel systems for local or systemic drug delivery in a sustained, controlled, and targetable manner has been at the epitome of recent advances in drug delivery systems. Cross-linked gels can be modified by altering their polymer composition and content for pharmaceutical and biomedical applications. These modifications have resulted in the development of stimuli-responsive and functionalized dosage forms that offer many advantages for effective dosing of drugs for Central Nervous System (CNS) conditions. In this review, the literature concerning recent advances in cross-linked gels for drug delivery to the CNS are explored. Injectable and non-injectable formulations intended for the treatment of diseases of the CNS together with the impact of recent advances in cross-linked gels on studies involving CNS drug delivery are discussed.